THE INFLUENCE OF BRAND IMAGE ON THE RELATIONSHIP BETWEEN PROMOTION AND LOYALTY TO SHOPEEFOOD CUSTOMERS IN BATUAJI BATAM Shandrya Victor Kamanda - Shandrya Victor Kamanda (LPPM Universitas Ibnu Sina, 2023)
Most business people expect loyalty from their customers, and ShopeeFood is no exception. This study aims to determine how promotion affects loyalty with brand image as a moderating variable. This study uses a quantitative approach with primary data obtained from respondents' responses through questionnaires and secondary data as reference material sourced from journals, articles, and books. The sample size was 98 respondents who were ShopeeFood customers in Batuaji Batam. Samples were taken based on purposive sampling method. Data analysis using SPSS tools. To test the hypothesis using multiple linear regression analysis and moderation variable interaction test analysis. The results showed that promotion has a positive and significant effect on loyalty, and brand image plays a role in strengthening the drive for loyalty. These results provide managerial implications for ShopeeFood to improve new strategies in promoting its products and strengthening its brand image so as to drive customer loyalty. Thus, ShopeeFood is expected to be able to plan the right strategy, attract and provide good service in order to create a positive brand image in the minds of consumers so that consumers have the potential to become loyal customers.